(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2021)
This study examines the relationship between the green-based school with students’ environmental attitudes and behavior. Sustainable development has become the solution and commitment to save the earth from destruction due to human behavior. Environmental education plays an important role in creating an environmentally literate society. Adiwiyata School, an official form of environmental education, is one of the efforts to increase sustainable development through education as a way to improve student’s environmental attitude and behavior. The research design used multiple case studies utilizing the observation method and questionnaire distribution to Adiwiyata and non-Adiwiyata schools. A New Ecological Paradigm (NEP) scale and a General Ecological Behavior (GEB) scale are used to measure student’s environmental attitudes and behavior change. As a result, the green-based school creates influences in student’s environmental attitudes (9.3%) and environmental behavior (12.3%).